Single-cell multi-omics and nursing follow-up prognostic modeling reveal SLFN4-mediated neutrophil dysregulation in traumatic brain injury - Tang, Wenping; Wang, Yang; Zhao, Fu; Hong, Yang; Wang, Lina; Xu, Wanyan; Ding, Fangfang; Shi, Tingting; Ke, Jing; Zhuang, Li; Wang, Yuan; Jia, Hongling; et al. (Frontiers in Immunology, 2025)
BackgroundTraumatic brain injury (TBI) is increasingly recognized as a systemic inflammatory disorder, with neutrophils playing a critical role in secondary injury. However, the phenotypic heterogeneity and clinical significance of neutrophil subsets in the early TBI immune landscape remain unclear, limiting their utility in nursing prognostic assessment and individualized care planning.MethodsWe performed an integrated multi-omics analysis—combining single-cell RNA sequencing (scRNA-seq), bulk transcriptomics, and proteomics—to dissect neutrophil diversity post-TBI. A distinct SLFN4+ neutrophil population was identified and further validated through in vitro functional assays and serum profiling in a TBI patient cohort. Clinical correlations and nursing stratification models were constructed to evaluate prognostic relevance.ResultsAt 24 hours post-injury, scRNA-seq revealed four neutrophil clusters in mouse brains. Among these, the SLFN4+ subset exhibited N1-like polarization, pro-inflammatory activation, and metabolic rewiring favoring glycolysis and oxidative phosphorylation. Regulon and pseudotime analyses highlighted its transitional regulatory potential. SLFN4+ neutrophils actively engaged in TNF and CCL-mediated communication with monocytes/macrophages. Functionally, silencing SLFN4 or STAT2 enhanced neutrophil proliferation and reduced inflammatory cytokine secretion. Clinically, elevated serum SLFN4 levels in TBI patients were associated with poor neurological outcomes and, when incorporated into a composite nursing risk model, significantly improved early prognostic accuracy.ConclusionsSLFN4+ neutrophils represent a key inflammatory effector population contributing to early immune dysregulation after TBI. Beyond mechanistic insights, SLFN4 serves as a promising serum biomarker to enhance clinical decision-making and nursing risk stratification. These findings support the integration of immunological biomarkers into precision nursing frameworks to guide early interventions and improve neurorehabilitation outcomes.